Globalisasi dan Hibridisasi Bahasa: Studi pada Penggunaan“Bahasa Gaul Jaksel” oleh Remaja di Media Sosial - Zulfa, Milatul; Fadhilah, Ninda Nurul; Harjono, Muhammad Budi (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
This article explores the role of social media in the dissemination and adaptation of South Jakarta slang (commonly known as Bahasa Gaul Jaksel) in Indonesia. The study employs a qualitative sociolinguistic approach, using documentation analysis based on screenshots of conversations on social media platforms. The findings reveal that Jaksel slang functions not only as a means of communication but also as a symbol of social status, identity, and modern cultural expression. Social media plays a crucial role in spreading this linguistic style, with platforms such as Twitter, Instagram, and TikTok serving as primary spaces where young people adopt new terms, engage in code-switching, and popularize English loanwords. Jaksel slang is characterized by the frequent use of English words such as literally, healing, or party, which are often adapted into everyday conversations. This phenomenon reflects both linguistic creativity and the social need among adolescents to appear trendy, follow current fashions, and gain acceptance within peer groups. Moreover, the use of Jaksel slang enhances self-confidence, expands social networks, and contributes to the construction of a social identity perceived as more modern and sophisticated. Nevertheless, alongside these positive dynamics of vocabulary enrichment and communicative flexibility, concerns arise that the dominance of global elements may erode local cultural identity. Overall, Jaksel slang represents a tangible manifestation of language hybridization in the era of globalization. It serves as a site of negotiation between local and global values, while highlighting the pivotal role of social media as a driver in shaping the linguistic identity of Indonesia’s younger generation. This phenomenon deserves ongoing scholarly attention, as it reflects broader social, cultural, and communicative transformations amid increasingly intensive global flows.